A Simulation Study on Pressure Control in Oil Well Drilling Using Gain-Scheduled PID Controllers - Alvarado-Silva, Carlos A.; de Oliveira, Geraldo Cesar Rosario [UNESP]; Gamboa, Alexander A. R.; Gaytan-Reyna, Karina Liliana; Guidi, Erick Siqueira [UNESP]; Silva, Fernando de Azevedo [UNESP]; Gamarra-Rosado, Victor Orlando [UNESP] (MDPI, 2025)
Controlling oil well pressure during drilling is one of the most complex and hazardous processes in the exploration stage. The drilling system undergoes constant variations, influenced by factors such as drilling depth, which in turn affects other process parameters. Consequently, applying a time-invariant control strategy becomes impractical. This study aimed to identify the PID parameters necessary to regulate bottom-hole pressure during drilling across different operating depths, with the goal of maintaining system stability and robustness. To achieve this, the parameters were tested using a Gain Scheduling (GS) controller, which adjusted the control gains according to various operating points. In the first section, the development of a mathematical model of the process, based on fluid mechanics, is presented. Linearizing this model introduced an integrating element, which complicated the process dynamics. In the second section, we present the design of the controller using the Internal Model Control (IMC) tuning methodology to address the integration challenges. Finally, PID parameters for different drilling depths were obtained and integrated into the GS controller via Matlab Simulink. The controller’s performance was then evaluated through simulations of typical drilling issues, such as simulated disturbances, confirming its viability. The GS-controlled system was compared to a system using an adaptive controller, demonstrating superior performance in the former.
Keywords: Gain Scheduling control; internal model control; PID parameters; pressure drilling control